7 Serial measurement of NT-PROBNP AND HS-CRP after acute coronary syndromes could identify patients with higher residual risk. (June 2018) - Ayton, Sarah; Michail, Olga; Bhatti, Maria; Gollop, Nicholas D; Ryding, Alisdair; Tang, Jonathan; Washbourne, Christopher; Nunney, Ian; Flather, Marcus
Abstract : Background: Serial measurement of NT-proBNP and high sensitivity C-reactive protein (hs-CRP) after an acute coronary syndrome (ACS) may help to identify patients at continuing risk of future events, although this is not currently recommended in guidelines. Methods: In patients with confirmed ACS we measured NT-proBNP and hs-CRP at 1, 3, 13 and 44 days after hospital admission to determine the proportion of patients with persistent elevation, as well as the pattern of biomarker evolution. Results: 56 patients were enrolled. Median age was 66.5 years, 73% were male and 39% had a discharge diagnosis of ST elevation myocardial infarction (MI). NT-proBNP peaked at day 1 (median 1040 pg/mL) and declined over time to 448 pg/mL at day 44 (p=0.002 compared to baseline), at which point 54% had elevated levels above the reference range (figure 1). At day 44 NT-proBNP levels were correlated with age (p=0.002), ST elevation (p=0.0003) and GRACE score (p=0.0002). hs-CRP rose from median 22 mg/L at day one to a peak of 2Sg/L at day 3, then declined to 6 mg/L at day 44 (p=0.0006 compared to baseline: figure 2). At day 44 hs-CRP levels were >2 mg/L in 77% and >10 mg/L in 34% of patients and were correlated with age (p=0.014) and GRACE score (p=0.01), but not ST elevation (p=0.4). There were no deaths or recurrent MI during follow up. Conclusions: We have demonstrated that although NT-proBNP and hs-CRP decline over time after ACS, more than half of patients have persistent elevation at 44 days after ACS. This may identify a group of patients at higher risk of future adverse cardiac events.